Local Level Collaborative Governance for Pandemic Responses: Unpacking A Case in Bangladesh - Ashraful Alam; Md Mahmudul Hoque (Indonesian Association for Public Administration, 2022)
Responsive governance during the COVID-19 pandemic became a severe challenge for countries worldwide. With a relatively poor healthcare structure, Bangladesh performed moderately well in managing the first wave of the pandemic (March – December 2020). With substantive policy and decision-making support from the Centre, local governments collaborated with various relevant actors to enhance their pandemic- related services. In this background, this research used an integrative framework to study a case of local-level collaborative governance – the Saturia Model. Based on the authors' experience, reflections and review, this analysis explores various socio-economic and environmental factors behind the effectiveness of this collaboration in containment policies and providing support services to vulnerable groups. Findings indicate that coordination between state and non-state actors, resource mobilization, access and communication, community engagement and the adaptative capacity of the government are vital for making such collaborations work in a crisis. The lessons are valuable for prospective understanding and policy interventions.